Leveraging Industry 5.0 Technologies for Building Resilience and Sustainability in the Oil and Gas Industry (American Journal of IR 4.0 and Beyond, 2025)
Amid growing environmental apprehensions, market volatility, and technological advancement, the oil and gas industry is confronted with the simultaneous demands of enhancing operational resilience and attaining sustainability goals. This study investigates the transformative influence of Industry 5.0 technologies on bolstering resilience and sustainability within the oil and gas sector. Industry 5.0, characterized by collaboration between humans and machines, advanced data analytics, artificial intelligence, robotics, and the Internet of Things (IoT), presents promising prospects for addressing these challenges. This research involves a detailed examination of 20 renowned global oil and gas companies that have embraced Industry 5.0 technologies. The paper examines how deploying key technologies affects these organizations’ resilience and sustainability. It highlights how these technologies enhance environmental resourcefulness, safety efficacies, and operational efficiency. Through the analysis of practical applications, the research showcases how Industry 5.0 integrations have empowered companies to uphold operational continuity, denigrate environmental footprints, and optimize resource utilization. The results underscore the pivotal role of Industry 5.0 in steering the oil and gas industry towards a more robust and sustainable trajectory, bestowing valuable insights for industry participants navigating the intricacies of a swiftly evolving global energy arena. Ultimately, the study underscores the indispensable nature of leveraging Industry 5.0 to secure enduring sustainability and resilience within the oil and gas domain.